Prevalence and sensitivity of bacilli and pseudomonas in the newborn’s oral cavity - Ferreira, Priscila Vitor Alves (2017)
The aim of this study was to isolate Enterobacteria and Pseudomonas from the oral cavity of hospitalized newborns (NB) and determine their prevalence and the sensitivity profile to most commonly used antibiotics for this age group. Samples from the oral cavity of NB from 24 to 48 h age were collected using swabs. The samples were inoculated on MacConkey agar, incubated and the colonies counted and identified. For each strain, the minimum inhibitory concentration (MIC) was determined using agar dilution test. Tests for enterobacteria producing extended spectrumβ-lactamases (ESBL) were performed using agar diffusion. Descriptive statistics was used for data analysis. Two of the isolated strains were submitted to the susceptibility test in biofilm. Of the collected samples, 8% presented Enterobacteria (mean of 6,141 CFU/mL) and no Pseudomona species was isolated. Positive samples were from NB in accommodation set or in the NB nursery. Enterobacter was the most prevalent genus and some strains were resistant to ampicillin, gentamicin and cephalothin. No ESBL strain was detected. Microorganisms in biofilms were resistant to all antibiotics, with concentrations four times higher than MIC. The presence of enterobacteria in the oral cavity of newborns, especially some strains resistant to normally used antibiotics, warns to the need for care to avoid the early colonization of this niche and the occurrence of a possible hospital infection in this age group.